Predictors of medical student interest and confidence in research during training: a cross-sectional study - Jennifer Klowak (Canadian Medical Education Journal, 2018)
Purpose: Research education and opportunities are an important part of undergraduate medical education. This study’s objectives were to determine students’ interest in research, student self-rated research skills and to assess potential predictors of research interest and confidence.